2012
DOI: 10.1007/s11095-012-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Necrosis, Fibrosis and Microsomal Activity Determine the Hepatic Pharmacokinetics of Basic Drugs in Right-Heart-Failure-Induced Liver Damage

Abstract: Serious hepatocellular necrosis and fibrosis induced by RHF affects both hepatic microsomal activity and hepatocyte wall permeability, leading to significant impairment in the hepatic pharmacokinetics of basic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Both reversible and fatal cases of DILI from labetalol have been reported . Labetalol is metabolised predominantly by glucuronosyl transferase, and PK data in rats suggest that in NASH, CYP P450 induction leads to increased hepatic removal of labetalol and other cationic beta blockers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Both reversible and fatal cases of DILI from labetalol have been reported . Labetalol is metabolised predominantly by glucuronosyl transferase, and PK data in rats suggest that in NASH, CYP P450 induction leads to increased hepatic removal of labetalol and other cationic beta blockers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the immaturity of kidney function in young infants, right-sided heart failure accompanied with PAH may result in decreased eGFR. On the other hand, Li et al 27 reported that liver sections from rats with right heart failure showed serious central lobular necrosis and sinusoid dilation and that CYP concentration significantly decreased in the livers of rats with right heart failure. Therefore, various factors might have affected CL int in the present data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Right‐sided heart failure or obstruction of the cranial vena cava leads to increased central venous pressure and passive venous hepatic congestion. Liver perfusion is impaired, and ischemia and necrosis occur . Chronically, this can lead to centrilobular fibrosis.…”
Section: Causes Of Hepatic Fibrosis In Dogsmentioning
confidence: 99%
“…Liver perfusion is impaired, and ischemia and necrosis occur. 98 Chronically, this can lead to centrilobular fibrosis. A similar pattern can develop after toxin ingestion.…”
Section: Causes Of Hepatic Fibrosis In Dogsmentioning
confidence: 99%